The influence of disturbance on driving carbon stocks and tree dynamics of riparian forests in Cerrado. (11th February 2017) - Nunes, Matheus Henrique; de Castro Nunes Santos Terra, Marcela; de Oliveira, Izabela Regina Cardoso; van den Berg, Eduardo
Abstract: Aims: Riparian forests in the Brazilian Cerrado, also known as gallery forests, are very heterogeneous in structure, species composition and ecological features due to strong and abrupt variations of soil, hydrological and topographic properties. However, what are the variables driving forest carbon stock and productivity, mortality and recruitment in disturbed gallery forests? Methods: We used 36 permanent plots data from a gallery forest in the Brazilian Cerrado. We investigated how tree community dynamics vary in a gallery forest on two contrasting disturbance levels—logged and non-logged—across a topographic gradient intrinsically related to differences in moisture conditions, edge effects, as well as soil fertility and texture. Important Findings: Soil variables were reduced into principal components and we used structural equation modelling to disentangle covarying variables. We also included carbon stocks as a determinant variable of dynamics rates. Logged forest had 50% higher productivity than non-logged forest and streamside forest had aboveground carbon stocks 70% higher than the forest edge. Both logging and natural disturbance drove variation in the carbon stocks which contributed to shaping productivity and recruitment rates. Distance from the river also drove mortality and carbon stock rates. Areas with high-carbon stocks favoured higher competition and lessened productivity and recruitment rates. Although soil fertility and texture are considered crucial components shaping forest dynamics, there was no clear influence of those variables on the present forest, probably because the strong effects of soil moisture, forest edge and disturbance disrupted the correlation between soil and forest dynamics.